Effect of Airborne-Particle Abrasion and Mechanico-Thermal Cycling on the Flexural Strength of Glass Ceramic Fused to Gold or Cobalt-Chromium Alloy - Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Silva, Lucas H. [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP]; Balducci, Ivan [UNESP]; Takahashi, Fernando Eidi [UNESP]; Bottino, Marco Antonio [UNESP] (Wiley-Blackwell, 2011)
Purpose: To evaluate the effect of airborne-particle abrasion and mechanico-thermal cycling on the flexural strength of a ceramic fused to cobalt-chromium alloy or gold alloy.Materials and Methods: Metallic bars (n = 120) were made (25 mm x 3 mm x 0.5 mm): 60 with gold alloy and 60 with Co-Cr. At the central area of the bars (8 mm x 3 mm), a layer of opaque ceramic and then two layers of glass ceramic (Vita VM13, Vita Zahnfabrick) were fired onto it (thickness: 1 mm). Ten specimens from each alloy group were randomly allocated to a surface treatment [(tungsten bur or air-particle abrasion (APA) with Al(2)O(3) at 10 mm or 20 mm away)] and mechanico-thermal cycling (no cycling or mechanically loaded 20,000 cycles; 10 N distilled water at 37 degrees C and then thermocycled 3000 cycles; 5 degrees C to 55 degrees C, dwell time 30 seconds) combination. Those specimens that did not undergo mechanico-thermal cyclingwere stored inwater (37 degrees C) for 24 hours. Bond strength was measured using a three-point bend test, according to ISO 9693. After the flexural strength test, failure types were noted. The data were analyzed using three factor-ANOVA and Tukey's test (alpha = 0.05).Results: There were no significant differences between the flexural bond strength of gold and Co-Cr groups (42.64 +/- 8.25 and 43.39 +/- 10.89 MPa, respectively). APA 10 and 20 mm away surface treatment (45.86 +/- 9.31 and 46.38 +/- 8.89 MPa, respectively) had similar mean flexural strength values, and both had significantly higher bond strength than tungsten bur treatment (36.81 +/- 7.60 MPa). Mechanico-thermal cycling decreased the mean flexural strength values significantly for all six alloy-surface treatment combinations tested when compared to the control groups. The failure type was adhesive in the metal/ceramic interface for specimens surface treated only with the tungsten bur, and mixed for specimens surface treated with APA 10 and 20 mm.Conclusions: Considering the levels adopted in this study, the alloy did not affect the bond strength; APA with Al(2)O(3) at 10 and 20 mm improved the flexural bond strength between ceramics and alloys used, and the mechanico-thermal cycling of metal-ceramic specimens resulted in a decrease of bond strength.
Keywords: Dental materials; airborne-particle abrasion; mechanical and thermal-cycling; chromium alloy; gold alloy; surface treatment; metal/ceramic joint